Efficacy and safety of temozolomide in the treatment of aggressive pituitary neuroendocrine tumours in Spain - Lamas, Cristina; Cámara, Rosa; Fajardo, Carmen; Remon-Ruiz, Pablo; Biagetti, Betina; Guerrero-Pérez, Fernando; Araujo-Castro, Marta; Mora, Mireia; Hanzu, Felicia; Iglesias, Pedro; García-Centeno, Rogelio; Soto, Alfonso (Frontiers in Endocrinology, 2023)
Current guidelines recommend temozolomide as the first-line chemotherapy for aggressive pituitary neuroendocrine tumours. However, no clinical trials have been conducted to date and clinical experience is quite limited. We retrospectively analyzed 28 patients (9 women and 19 men), aged 46.6 + 16.9, with aggressive pituitary tumours (4 pituitary carcinomas and 24 aggressive adenomas) treated with temozolomide in 10 Spanish pituitary reference centres. Four patients had Cushing’s disease, 9 prolactinomas and 15 clinically non-functioning pituitary tumours (seven silent corticotroph, three silent somatotroph, one silent lactotroph, one silent gondotroph and three null-cell tumours). Median size at diagnosis was 10.5 cm3 (IQR 4.7-22.5), with cavernous sinus invasion in 88% and no metastases. Pre-temozolomide treatment, these data were 5.2 cm3 (IQR 1.9-12.3), 89.3% and 14.3% (2 intracranial and 2 spinal metastases). All patients had undergone surgery (1-5 surgeries), 25 (89.3%) had received radiotherapy (7 of them reirradiated) and 13(46.4%) had received cabergoline. One patient interrupted temozolomide prematurely. The remaining 27 patients received a median of 13 cycles (range 3-66) of 5 days every 28 days, with a mean initial dose of 265 ± 73 mg when administered alone and of 133 ± 15 mg when co-administered with radiotherapy. Eight patients (29.6%) had a significant reduction (>30%) in tumour volume and 14 (51.9%) attained tumour stabilization. After a median follow-up of 29 months (IQR 10-55), 8 out of these 22 showed disease progression. A longer progression-free survival was found in the five patients who received concomitant radiotherapy. Seven patients (25%) died (all of them because of tumour progression or complications of treatments) at 77 months (IQR 42-136) after diagnosis and 29 months (IQR 16-55) after the first dose of temozolomide. Adverse effects occurred in 18 patients (14 mild and 4 moderate or severe). In conclusion, temozolomide is an effective medical treatment for aggressive pitNET and pituitary carcinomas but is sometimes followed by tumour progression. Co-administration with radiotherapy may increase progression-free survival.